Interaction of Acinetobacter sp. RIT 592 induces the production of broad-spectrum antibiotics in Exiguobacterium sp. RIT 594 - Parthasarathy, Anutthaman; Miranda, Renata Rezende; Bedore, T. J.; Watts, Lizabeth M.; Mantravadi, Pavan K.; Wong, Narayan H.; Chu, Jonathan; Adjei, Joseph A.; Rana, Amisha P.; Savka, Michael A.; Bulman, Zackery P.; Borrego, Eli J.; et al. (Frontiers in Pharmacology, 2024)
Antimicrobial resistance (AMR) is one of the most alarming global public health challenges of the 21 st century. Over 3 million antimicrobial-resistant infections occur in the United States annually, with nearly 50,000 cases being fatal. Innovations in drug discovery methods and platforms are crucial to identify novel antibiotics to combat AMR. We present the isolation and characterization of potentially novel antibiotic lead compounds produced by two rhizosphere bacteria, Acinetobacter sp. RIT 592 and Exiguobacterium sp. RIT 594. The supernatant from RIT 592 induced RIT 594 to produce a cocktail of antimicrobial compounds active against Gram-positive and negative bacteria. The antibiotic constituents were enriched using solid-phase extraction (SPE), followed by liquid chromatography (LC) and subsequent mass spectrometry (MS) analysis of collected fractions for compound structure identification and characterization. The MS data were processed through the Global Natural Product Social Molecular Networking (GNPS) database, indicating compounds with known antimicrobial activity in the bioactive samples, including oligopeptides and their derivatives. This work emphasizes the utility of microbial community-based platforms to discover novel clinically relevant secondary metabolites. Future work includes further structural characterization and antibiotic activity evaluation of the individual compounds against pathogenic multidrug-resistant (MDR) bacteria.